The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0229993
|View full text |Cite
|
Sign up to set email alerts
|

Plasma virome of 781 Brazilians with unexplained symptoms of arbovirus infection include a novel parvovirus and densovirus

Abstract: Plasma from patients with dengue-like symptoms was collected in 2013 to 2016 from the Brazilian states of Tocantins and Amapa. 781 samples testing negative for IgM against Dengue, Zika, and Chikungunya viruses and for flaviviruses, alphaviruses and enteroviruses RNA using RT-PCRs were analyzed using viral metagenomics. Viral particles-associated nucleic acids were enriched, randomly amplified, and deep sequenced in 102 mini-pools generating over 2 billion reads. Sequence data was analyzed for the presence of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 79 publications
1
17
0
Order By: Relevance
“…However, while the phylogenetic placement of the DAC sequences within a clade that is dominated by avian viruses within a genus that includes many vertebrate viruses, some of which even proven to be pathogenic [ 47 , 48 ], clearly points towards ducks as DAC hosts, such a clear conclusion cannot be made for DAAD. Densoviruses are frequently identified during metagenomic investigations of samples collected from vertebrates [ 43 , 44 , 49 ], including human plasma and cerebrospinal fluid [ 50 , 51 ], and some of the densoviruses genetically close to DAAD were also vertebrate-associated as they were detected in fecal specimens of birds, monkeys, and bats [ 43 , 44 ]. However, dipteran and lepidopteran viruses were also included in the same clade as DAAD and no proof exists that densoviruses can replicate in vertebrate hosts.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the phylogenetic placement of the DAC sequences within a clade that is dominated by avian viruses within a genus that includes many vertebrate viruses, some of which even proven to be pathogenic [ 47 , 48 ], clearly points towards ducks as DAC hosts, such a clear conclusion cannot be made for DAAD. Densoviruses are frequently identified during metagenomic investigations of samples collected from vertebrates [ 43 , 44 , 49 ], including human plasma and cerebrospinal fluid [ 50 , 51 ], and some of the densoviruses genetically close to DAAD were also vertebrate-associated as they were detected in fecal specimens of birds, monkeys, and bats [ 43 , 44 ]. However, dipteran and lepidopteran viruses were also included in the same clade as DAAD and no proof exists that densoviruses can replicate in vertebrate hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Parvoviruses are associated with disease in a variety of host species, ranging from canines [ 47 ] to livestock [ 48 , 49 , 50 , 51 ], rodents [ 36 ], and humans [ 52 ]. Reptile parvoviruses were identified in several snake species (snake adeno-associated virus) [ 11 , 53 , 54 , 55 , 56 , 57 ] and some lizard species including bearded dragons [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, B19V is the most frequent cause of rash/fever infections in cases where serum testing is negative for arboviruses and rubella, and several studies have shown an increase in PB19 rash/fever cases in a spatiotemporal manner compared to arboviruses and rubella [ 243 , 244 ]. Parvovirus B19 has been detected in 17% of cases when assaying the plasma of Brazilian patients with dengue fever-like symptoms, while samples were negative for arbovirus and were originally misdiagnosed (falsely positive for DENV) [ 245 , 246 , 247 , 248 , 249 ], A similar trend has also been reported for ZIKV [ 52 , 250 , 251 ].…”
Section: Human Latent Virus (Hlv) Selection With Common Interests In Czsmentioning
confidence: 79%